UK policy statements on testosterone deficiency. Issue 3 (20th March 2017) - Hackett, Geoffrey; Kirby, Michael; Edwards, David; Jones, T. Hugh; Rees, Jonathan; Muneer, Asif
Summary: To address widespread media and scientific concerns over the appropriate treatment of TDS with Testosterone Therapy (T Therapy), the Executive Committee of the British Society for Sexual Medicine developed eight consensus statements, based on current scientific evidence to address these controversial issues. These statements were in no‐way designed to replace the published evidence‐based guidelines on the subject developed by various professional organisations, but to provide specific answers to several current controversial issues. This review examined evidence from Medline, EMBASE and Cochrane searches on HG, T Therapy and cardiovascular safety from May 2005 to May 2015, which revealed 1714 articles, with 52 clinical trials and 32 placebo‐controlled randomised controlled trials. The task force developed the following eight key statements.